#### Answer

(x+3)(x+10)

#### Work Step by Step

$x^{2}$ + 13x + 30 = (x+3)(x__)
step 1. Enter x as the first term of each factor
$x^{2}$ + 13x + 30 = (x+3)(x__)
Step 2. To find the second term of each factor, we must find two integers whose product is 30 and whose sum is 13
List pairs of factors of the constant, 30
(1,30)(5,6)(15,2)(10,3)
step 3. The correct factorization of x2 + 2x - 35 is the one in which the sum of the Outside and Inside products is equal to 13x.
So (10,3) satisfy the condition
$x^{2}$ + 13x + 30 = $x^{2}$ +10x+3x + 30 = (x+10)(x+3)